Observations of the Electromagnetic Electron Kelvin‐Helmholtz Instability and Its Impact on the Dynamics Inside a Flux Rope - K. Jiang; S. Y. Huang; Q. M. Lu; Z. G. Yuan; Q. Y. Xiong (Geophysical Research Letters)
Abstract The electromagnetic electron Kelvin‐Helmholtz instability (EM EKHI) and its impact on the dynamics inside a flux rope (FR) is investigated through observations from the Magnetospheric Multiscale mission. The convection term dominated electric field drives E × B drift in the FR, which supports a strong electron shear flow. The electron shear flow is unstable to the EM EKHI, which results in an electron velocity vortex and many current filaments in the FR. In one of the current filaments, ion and electron demagnetization and strong energy conversion are observed. The continuous radial nulls and obvious reconstructed X‐line topology indicate that magnetic reconnection may occur in this current filament.